A Comparison of Oral Health Outcomes of Self-Reported and Agency-Notified Child Maltreatment in a Population-Based Birth Cohort at 30-Year-Old Follow-Up. Issue 2 (February 2022) - Kisely, Steve; Strathearn, Lane; Najman, Jake Moses
ABSTRACT: Objective: Information on the oral health outcomes of childhood maltreatment in adulthood is limited and reliant on retrospective questionnaires that are subject to recall bias. There are no data from prospective studies using maltreatment reports to statutory agencies. We therefore assessed the effect on dental outcomes and oral health care at 30-year follow-up using both prospective agency notifications and retrospective self-reports of child maltreatment in the same birth cohort. Methods: There were 2456 adults with data on dental outcomes and oral health care at follow-up. Information on self-reported abuse was collected using the Child Trauma Questionnaire and linked to child maltreatment notifications to statutory agencies. Results: The prevalence of self- and agency-reported maltreatment was 599 (24.4%) and 142 (5.8%), respectively. At follow-up, 850 participants (34.6%) had undergone a dental extraction for infection or decay, and 810 had experienced significant dental pain over their lifetime. One-third had not visited a dental clinic in the previous 2 years, and 40% failed to brush their teeth at least twice daily. On adjusted analyses, both self- and agency-reported maltreatment showed significant associations with dental extraction (odds ratio = 1.47 [95% confidence interval = 1.21–1.80] and odds ratio = 1.44 [95% confidence interval = 1.01–2.06], respectively). There were similar results for brushing frequency, whereas self-reported maltreatment was associated with dental pain. However, associations were weaker for dental clinic visits and some child maltreatment subtypes. Conclusions: Child maltreatment is associated with adverse oral health consequences in adulthood and is thus a dental and wider public health issue. Abstract : Supplemental digital content is available in the text.